Influence of Solution Treatment Process on the Properties of Duplex Stainless Steels: A Comparative Study on Microstructure and Corrosion Properties of UNS S32205 and UNS S32760 - Tütük, İbrahim; Ural, Mehmet Moğoltay; Özer, Gökhan; Kısasöz, Alptekin (Springer, 2024)
The study investigated the effect of the solution treatment process on the corrosion behavior and microstructure of the duplex stainless steel. It was also aimed to reveal this effect comparatively depending on the chemical composition and alloying element content. For this purpose, UNS S32205 and UNS S32760 alloys were treated at 1000 C, 1020 C and 1040 C for an hour. A solution treatment temperature was determined according to Thermo-Calc analysis. The examined samples were characterized by an optical microscope, scanning electron microscope, and XRD analysis. Also, electrochemical impedance spectroscopy and potentiodynamic polarization analyses revealed the corrosion properties of solution-treated samples. Microstructural studies showed that enhanced solution treatment temperature increased ferrite content for both alloys. A lower solution treatment temperature caused the formation of sigma in the microstructure of S32760 alloy. On the other hand, the charge transfer resistance of the passive layer was reduced after solution treatment at 1000 C and 1020 C, indicating decreasing corrosion resistance. A higher austenite ratio in S32205 led to pitting, while corrosion resistance improved with higher treatment temperatures. The presence of the sigma phase in S32760 significantly impacted corrosion properties by increasing ion transfer on the surface, leading to reduced corrosion resistance. It was determined that solution treatment at 1040 C was appropriate for both alloys to achieve the desired microstructure and corrosion properties.